Superalloys 2012 2012
DOI: 10.1002/9781118516430.ch64
|View full text |Cite
|
Sign up to set email alerts
|

Laser Powder Bed Fabrication of Nickel‐Base Superalloys: Influence of Parameters; Characterisation, Quantification and Mitigation of Cracking

Abstract: The use of a selective laser melting (SLM) powder-bed method to manufacture Ni-based superalloys components provides an economic approach for low production run components that operate under a high-temperature and stress environment. A major concern with the SLM of precipitation hardenable Ni-based superalloys is their high susceptibility to cracking, which has been heavily documented in the field of welding. Weld cracking may occur either during processing (hot cracking, liquation cracking and ductility-dip c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 36 publications
(42 reference statements)
2
55
1
1
Order By: Relevance
“…Recently, there is a strong research activity to qualify these kinds of alloys for processing by additive manufacturing. [13][14][15] In Reference 16 we have demonstrated that crack-free processing of CMSX-4 Ò via selective electron beam melting is possible. Even single crystals emerged directly from the powder bed by applying a suitable processing strategy.…”
Section: Cmsx-4mentioning
confidence: 99%
“…Recently, there is a strong research activity to qualify these kinds of alloys for processing by additive manufacturing. [13][14][15] In Reference 16 we have demonstrated that crack-free processing of CMSX-4 Ò via selective electron beam melting is possible. Even single crystals emerged directly from the powder bed by applying a suitable processing strategy.…”
Section: Cmsx-4mentioning
confidence: 99%
“…The LPBF process has been successfully employed for the fabrication of dense components made of various Ni-based superalloys such as Inconel 625 and Inconel 718 [9,12,13]. However, several Ni-based superalloys are prone to cracking during the LPBF due to their low weldability or the inappropriate selection of process parameters [2,4,14,15,16,17]. For instance, Hastelloy X (HX) alloy is characterized by susceptibility to crack formation when processed by LPBF [2,18,19,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…High c¢ volume fraction materials are susceptible to crack formation especially to strain age cracking and are typically considered as hard-or not weldable. [12][13][14] Because of their high cracking susceptibility, it is a challenge to process materials like CMSX-4 by additive technologies. [15,16] In the literature, investigations on IN625, IN738, and Rene142 as representative materials with high c¢ volume can be found.…”
Section: Introductionmentioning
confidence: 99%